Verso un nuovo diritto penale sessuale Diritto vivente, diritto comparato e prospettive di riforma della disciplina dei reati sessuali in Italia - Macrì, Francesco (Premio Tesi di Dottorato, 2010)
This book is centred on the proposal of a new organic criminal discipline for sexual offences in Italy. The Foreword introduces innovative concepts and 'general' breakdowns relating to sexual criminal law. Chapter 1 then addresses a critical analysis of the current discipline, pursuant to articles 609-bis and following of the Criminal Code and the related case law. Chapter 2 tables an in-depth comparative analysis of the legislation governing sexual offences in Germany, Portugal, France and England, which is also extended to legal theory and practice. Chapter 3 then presents, complete with detailed commentary, an organic project of reform for Italian legislation, characterised by a total discontinuity with the current discipline, where the principal incriminations hinge upon the mere 'sexual dissent' of the victim, breaking down different types of sexually relevant behaviour that are at present all lumped in together in the melting-pot of "sexual assault" into three different offences, while also introducing other incisive innovations.